The effect of outdoor education intervention to improve leadership among students: a systematic review - Yang, Xiaoming; Samsudin, Shamsulariffin; Wei, Shasha; Guo, Qi; Soh, Kim Geok; Yaakob, Sam Shor Nahar (St. Davids PA, 2023)
Outdoor education is an emerging form of physical education that is widely practiced in students, especially among physical education undergraduates. However, there is a lack of a systematic review focused on the leadership of students participating in outdoor education. Leadership is essential for motivating followers and mobilizing resources to achieve the organization's mission; it is also necessary for organizational innovation, adaptation, and performance. Thus, the present review aims to clarify the leadership of students participating in outdoor education. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) Statement guidelines. Searched four databases of PUBMED, SCOPUS, EBSCO host (SPORT Discus) and Science Direct databases were undertaken on July 2022 to find 11 articles that met the criteria. Data were extracted using the PICOS extraction tool and summarized using a narrative synthesis approach. Studies have shown that outdoor education could increase leadership (decision-making, communication, self-effective, cooperation, group work skill, active initiative and time management, responsibility, influence, self-confidence, planning, organization, etc.) among students. There are no uniform norms and standards for researchers in developing outdoor education time and programs, and most of them are based on their own experience and existing sites and facilities, and this is the key issue to be addressed.